2019
DOI: 10.1111/1750-3841.14672
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sourdough Fermentation on Non‐Nutritive Compounds and Antioxidant Activities of Flours from Different Phaseolus Vulgaris L. Genotypes

Abstract: This study dealt with the effect of sourdough fermentation on antinutrients, phytochemicals, and antioxidant activities of flours from three Phaseoulus vulgaris L. genotypes with differing composition of lectins. Specifically, cultivar Lady Joy (LJ) devoid of phytohemagglutinin (PHA) and enriched in alfa‐amylase inhibitor (αAI), breeding line P500 low in PHA and devoid of αAI, and Taylor's horticultivar, containing normal levels of both proteins. Sourdough fermentation positively affects the nutritional values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Microbial metabolism of kefir grains and hydrolysis of the bonds between phenolic compounds and structural carbohydrates increase the phenolic compounds (Bei, Chen, Lu, Wu, & Wu, 2018). The effect of fermentation on the nutritional properties of wheat flour was a significant increase in the levels of total phenolic compounds, justifying that fermentation can improve the nutritional characteristics of foods (Gabriele et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Microbial metabolism of kefir grains and hydrolysis of the bonds between phenolic compounds and structural carbohydrates increase the phenolic compounds (Bei, Chen, Lu, Wu, & Wu, 2018). The effect of fermentation on the nutritional properties of wheat flour was a significant increase in the levels of total phenolic compounds, justifying that fermentation can improve the nutritional characteristics of foods (Gabriele et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Also, the extract of few sourdoughs decreased the proliferation of human adenocarcinoma Caco-2 cells viability up to 70%. The experimental work of Gabriele et al (2019) showed that sourdough fermentation of bean flours significantly increased ascorbic acid, flavonols, total polyphenols, and reduced phytic acid content. The antioxidant activities of the fermented product demonstrated a strong inhibitory effect on low-density lipoproteins oxidation.…”
Section: The Current State Of Research On 3d Printed Foods and Applicability For Fermented And Malted Foodsmentioning
confidence: 99%
“…Yeast and LAB fermentation has been found to reduce the amount of phytic acid in faba bean [85], common bean [86], and soybean [87][88][89], for example. Furthermore, the reduction in phytic acid by LAB fermentation (e.g., strains L. acidophilus B4496, L. bulgaricus CFR2028, L. casei B1922, L. plantarum B4495, and L. fermentum B4655; 37 • C, 24 h) has been suggested to increase the Ca and Mg availability in soymilk [89].…”
Section: Fermentation Increases Nutrient Availability In Commonly Conmentioning
confidence: 99%